The Urgency of the Indigenous Peoples Bill: Developing a Legal Framework for the Protection of Environmental Activists in Indonesia - Wijaya, I Ketut Kasta Arya; Azhar, Ali; Ridwan, Muannif; Fikri, KMS. Novyar Satriawan; Siregar, Vivi Ariani; Siagian, Ruben Cornelius (The Republic of Indonesia Defense University, 2025)
The research investigates the challenges faced by environmental and indigenous activists in Indonesia, focusing on how legal and institutional frameworks contribute to criminalization and repression. Using a qualitative case study approach, the research analyzed several landmark cases, including those of Daniel Frits Tangkilisan, Jasmin, and others, to identify recurring patterns of legal intimidation, particularly through the misuse of defamation and subversion provisions. These cases were selected based on their representativeness and relevance to broader trends observed in environmental conflicts involving indigenous peoples. The research identified systemic gaps in legal protection for environmental defenders by tracing the legal trajectory and socio-political context surrounding the incidents. These gaps allow industrial interests to suppress dissent and perpetuate ecological damage without adequate accountability. The findings demonstrate the interconnectedness of these patterns, exposing a broader legal and political landscape that fails to adequately safeguard human rights and environmental justice. The research contributes to academic discourse by offering a critical reflection on how existing legal instruments in Indonesia fail to address these issues. It argues that the passage of the Indigenous Peoples Bill could be an important step toward institutional reform by strengthening legal protections, enabling participatory resource governance, and reducing the criminalization of legitimate advocacy efforts. The novelty of this research lies in the analytical link between individual case dynamics and structural legal deficiencies, which provides a framework for policy discussions rooted in empirical evidence and grounded analysis.